A Rat Experimental Model for Investigation of the Effect of Diabetes on Submandibular Salivary Glands Treated with Epidermal Growth Factor - Bakr, Mahmoud; Shamel, Mohamed; Elwahed, Sara Abd; Al Ankily, Mahmoud (Open Access Macedonian Journal of Medical Sciences, 2022)
Background: Despite the plethora of research around the negative effects of diabetes on different body organs, this topic still attracts a lot of attention in order to find potential remedies that could counteract or reverse the damaging effect of diabetes. Aim: In this study, we developed a reliable experimental rat model that can be used for investigation of the ability of epidermal growth factor (EFG) in restoring the normal architecture of oral tissues after being damaged by diabetes. Methods: Eighty adult male albino rats (average weight ±220 gm) were used in the current study. Twenty rats served as control and received no treatment. Diabetes was induced in forty rats using a single injection of 65mg/kg of Streptozotocin (STZ). Out of the forty diabetic rats, twenty rats received a single daily intraperitoneal injection of EGF (10 µg/Kg) for 8 weeks. Furthermore, twenty healthy rats received the same dose of EGF and served as positive controls. The submandibular salivary glands of all rats were examined for Immunohistochemical detection of myosin in the glandular structure. Results: The EGF treated group showed comparable myosin expression to the control group. The diabetic group revealed deterioration of all components of the submandibular salivary glands. Finally, the diabetic + EGF group has demonstrated restoration of the myosin expression levels in the submandibular salivary glands to a level that is not significantly different from healthy (non-diabetic) rats in the control group (p>0.05) and significantly higher than the diabetic group (p<0.0001). Conclusion: The findings of the present study confirm previous studies and validates the use of our animal model as predictable experimental tool to investigate the effects of diabetes and EGF on different oral tissues. It also highlights the importance of further research investigating EGF as a promising treatment modality for restoration of the condition and functions of tissues damaged by diabetes not only in the oral cavity but also around the whole body.